Nilai-Nilai Pendidikan Berbasis Karakter Islam pada Pendidikan Dasar - Atsmarina Awanis (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Issues about the decline in moral values in society and the school environment are still often heard. One of the reasons is the lack of success in implementing moral values, especially among students. Referring to this fact, the teaching system at MI Kampung Santri Kebumen collaborates the independent curriculum with religious learning which focuses on learning the Koran. The aim of this research is to examine how the education system at MI Kampung Santri Kebumen applies educational character. The research method used is a qualitative descriptive method with observation and documentation data collection techniques. The results of this research show that several habits such as saying hello and shaking hands with teachers when entering the school gate, reading Asmaul Husna in the morning, praying before and after learning, studying the Koran in the morning have been implemented every day. day. With this habituation and teaching, students can be formed into individuals who are virtuous, have noble character and have high knowledge. Creating this habit requires support from all elements in the school environment.